Theoretical Basics of Ensuring Food Security of the Country - Samiyeva Gulnoza; Ochilova Maftuna (International Journal on Economics, Finance and Sustainable Development, 2022)
The article reveals the importance of ensuring food safety and the practical aspects of consistent reforms in this regard in our country.